Electrochemical Formation in Super-Concentrated Phosphonium Based Ionic Liquid Electrolyte Using Symmetric Li-Metal Coin Cells. Issue 12 (26th August 2020) - Pathirana, Thushan; Kerr, Robert; Forsyth, Maria; Howlett, Patrick C.
Abstract : Electrochemical pre-conditioning, also known as formation cycling, is a key step in forming a stable solid electrolyte interphase (SEI) on the anode in Li-ion batteries. This process is costly, time consuming and one of the bottlenecks in battery manufacture. However, studies of electrochemical pre-conditioning for use with high specific energy lithium metal batteries is limited. In this study, lithium metal electrodes were cycled in a super-concentrated phosphonium bis(fluorosulfonyl)imide ionic liquid electrolyte, demonstrating stable cycling and good rate performance at practical cycled capacities. Electrochemical pre-conditioning regimes were applied for 5 cycles in a Li∣Li symmetrical coin cell configuration using a range of current densities (up to 10 mA cm −2 ) and coupled with different depths of charge (up to 5 mAh cm −2 ). Higher currents and depths of charge resulted in a more compact and uniform lithium deposit which cycled with lower cell overpotentials under long-term (1 mA cm −2 ∣1 mAh cm −2 ) conditions. The long-term cell cycling stability and performance was further improved by applying a pulsed high current pre-conditioning method, which further homogenized and smoothed the lithium morphology. Compared to formation at lower current density, pre-conditioning using a high current density pulse reduced the formation time by 50%, offering a pathway to reduced-cost lithium metal battery manufacturing.